Composição físico-química, perfil fenólico e atividade antioxidante de pitanga (Eugenia iniflora L.) de cor alaranjada e roxa - Barreira, Rooslany Queiroz (2024)
The pitangueira (Eugenia uniflora L.) is a fruit tree native to Brazil, which contains high concentrations of bioactive compounds and high antioxidant capacity. This species has fruits that vary in color from orange-yellow, various shades of red to purplish-black. The present work aimed to investigate the physicochemical characteristics, the profile of phenolic compounds and the antioxidant capacity of two pitangueira genotypes, comparing fruits with orange and purple cores. The pitangas were evaluated in relation to their physicochemical characteristics, then the ethanolic extracts were prepared for analysis of concentration of total anthocyanin compounds, total phenolic compounds, determination of antioxidant activity by three methods (DPPH, FRAP, ABTS), and the and phenolic profile using high-performance liquid chromatography, with a diode array detector (HPLC-DAD). The results were tested to compare the means between the fruits of the two genotypes. Orange pitangas showed higher titratable acidity and color parameters (L*, b*, C* and h). Purple pitangas showed higher pH values, soluble solids/titratable acidity ratio, total anthocyanins, total phenolic compounds and antioxidant activity by the ABTS method. The compounds gallic acid, chlorogenic acid, quercetin and rutin were found in pitangas of both colors, with concentrations 2,2 to 3,4 times higher in purple pitangas. Furthermore, three compositions (catechin, epicatechin and isoquercetin) were presented only in purple pitangas. These results indicate that purple pitanga has greater bioactive and therapeutic potential, as it presented a higher content of anthocyanins and phenolic compounds from the class of flavonoids, polyphenols and tannins, resulting in greater antioxidant activity.